2018
DOI: 10.1177/2042098618781524
|View full text |Cite
|
Sign up to set email alerts
|

Shed-MEDS: pilot of a patient-centered deprescribing framework reduces medications in hospitalized older adults being transferred to inpatient postacute care

Abstract: A hospital-based, patient-centered deprescribing intervention is feasible and may reduce the medication burden in older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 39 publications
(58 reference statements)
0
30
0
Order By: Relevance
“…Among the 3 studies focusing on the use of protocols, algorithms, and clinical decision support systems to promote deprescribing, 2 studies found significant decreases in the number of medications prescribed. Petersen et al 19 found that a patient-centered deprescribing protocol called Shed-MEDS, implemented in 4 phases: (1) medication history and list confirmed, (2) evaluate medication for deprescribing, (3) decide with the patient, and (4) synthesize and communicate recommendations among Medicare beneficiaries prescribed 5 or more medications, significantly reduced the mean number of prescribed medications from 11.6 to 9.1 ( P = 0.032) for those with whom the protocol was used. Garfinkel and Mangin 14 worked with elderly patients in Israel to implement the Good Palliative-Geriatric Practice algorithm, an evidence-based flowchart for medication discontinuation, which recommended discontinuing a total of 311 medications for 64 patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the 3 studies focusing on the use of protocols, algorithms, and clinical decision support systems to promote deprescribing, 2 studies found significant decreases in the number of medications prescribed. Petersen et al 19 found that a patient-centered deprescribing protocol called Shed-MEDS, implemented in 4 phases: (1) medication history and list confirmed, (2) evaluate medication for deprescribing, (3) decide with the patient, and (4) synthesize and communicate recommendations among Medicare beneficiaries prescribed 5 or more medications, significantly reduced the mean number of prescribed medications from 11.6 to 9.1 ( P = 0.032) for those with whom the protocol was used. Garfinkel and Mangin 14 worked with elderly patients in Israel to implement the Good Palliative-Geriatric Practice algorithm, an evidence-based flowchart for medication discontinuation, which recommended discontinuing a total of 311 medications for 64 patients.…”
Section: Resultsmentioning
confidence: 99%
“…More rigorous, long-term studies with larger sample sizes are needed to further understand deprescribing interventions long-term effects in reducing polypharmacy and preventable ADEs. 12 , 17 , 19 Studies would also be improved if they examined clinical outcomes, not just process or intermediate outcomes. Comparative effectiveness study of different deprescribing interventions, whether single or multicomponent would also be beneficial to the field.…”
Section: Discussionmentioning
confidence: 99%
“…describe effective hospital inpatient programs focused on deprescribing prior to discharge. 2224 Similarly Garfinkel showed positive effects of deprescribing that were sustained longitudinally in a community setting. 25 How to maintain this focus in busy services focused on the multiple needs of complex patients is the challenge.…”
Section: For the International Group For Reducing Inappropriate Medicmentioning
confidence: 98%
“…13 When evaluating medications, clinicians and patients face complex trade-offs which can lead to an emphasis on preference-sensitive decisions. 14,15 There is evidence that taking into account patient goals and preferences improves outcomes 16 and this seems particularly important for optimizing medicines for older patients. 14 Even though patients vary in their preference for involvement in health decisions, most older people want their perspectives to be heard, 17 so it is important for health care professionals to support communication and create opportunities for this.…”
Section: Resultsmentioning
confidence: 99%